Extracellular DNA metabolism in Haloferax volcanii - Chimileski, Scott; Dolas, Kunal; Naor, Adit; Gophna, Uri; Papke, R Thane (Frontiers in Microbiology, 2014)
Extracellular DNA is found in all environments and is a dynamic component of the micro-bial ecosystem. Microbial cells produce and interact with extracellular DNA through many endogenous mechanisms. Extracellular DNA is processed and internalized for use as genetic information and as a major source of macronutrients, and plays several key roles within prokaryotic biofilms. Hypersaline sites contain some of the highest extracellular DNA con-centrations measured in nature–a potential rich source of carbon, nitrogen and phosphorus for halophilic microorganisms. We conducted DNA growth studies for the halophilic archaeon Haloferax volcanii DS2 and show that this model Halobacteriales strain is capable of using exogenous double-stranded DNA as a nutrient. Further experiments with varying medium composition, DNA concentration and DNA types revealed that DNA is utilized primarily as a phosphorus source, that growth on DNA is concentration-dependent and that DNA isolated from different sources is metabolized selectively, with a bias against highly divergent methylated DNA sources. Additionally, fluorescence microscopy experiments showed that labeled DNA colocalized with Haloferax volcanii cells. The gene Hvo_1477 was also identified using a comparative genomic approach as a factor likely to be involved in extracellular DNA processing at the cell surface, and deletion of Hvo_1477 created an H. volcanii strain deficient in its ability to grow on extracellular DNA. Widespread distribution of Hvo_1477 homologs in archaea suggests metabolism of extracellular DNA may be of broad ecological and physiological relevance in this domain of life.